NICKEL ADMINISTRATION AND CHANGES OBSERVED IN GROSS APPEARANCE, MORPH METRIC/HISTOLOGICAL PARAMETERS OF ALBINO RAT AND ITS LIVER TISSUE - Saif ud Din; Muhammad Waqar Faisal; Muhammad Aslarn (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: The study was carried out to assess the changes observed in gross appearance and morphometric/Histological parameters in albino rats and their liver tissue on Nickel administration. STUDY DESIGN: Experimental study. SETTINGS AND DURATION OF STUDY: Animal House PGMI Lahore, thirty days. MATERIAL AND METHODS: Thirty two adult Albino rats were taken and kept for study at animal house PGMI, Lahore. They were divided into two control groups; A1 and A2 and two experimental groups B1 and B2 (each having eight animals). Control group were given intra peritoneal (I/P) injection of distilled water 1 ml /kg body wt/day for the duration corresponding to their experimental group. Experimental groups (B1 & B2) were given I/P Injections of Nickel chloride (NiCl2) 2µg/kg body wt/day for 15 and 30 days respectively. RESULTS: 1. Irritability and reduction in diet intake towards the end of experiment. 2. Significant decrease in body weight and growth rate in experimental group B2 3. Enlargement of liver and significant increase in relative tissue weight index (RTWI) in both experimental groups. 4. Morphometric/histological parameters showed significant changes in experimental groups. CONCLUSION: Nickel administration beyond the permissible limits is deleterious for both gross and morphometric/histological parameters.